2021
DOI: 10.1111/ene.15137
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant use and stroke or mortality risk in the elderly

Abstract: Background and purpose: Current evidence on antidepressant-related stroke or mortality risk is inconsistent. Because the elderly have the highest exposure to antidepressants, the aim was to quantify their association with stroke and mortality risks in this vulnerable population. Methods: Persons over 65 years old and registered in the Information System for Research in Primary Care of Catalonia during 2010-2015 comprised the study population. Antidepressant exposure was categorized into current-users, recent-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The second most common cause of uncertain death around the world is stroke. It is also the primary cause of permanent neurodisability [ 1 , 2 ]. About 17 million stroke cases occur worldwide each year.…”
Section: Introductionmentioning
confidence: 99%
“…The second most common cause of uncertain death around the world is stroke. It is also the primary cause of permanent neurodisability [ 1 , 2 ]. About 17 million stroke cases occur worldwide each year.…”
Section: Introductionmentioning
confidence: 99%
“…There are also studies showing that the risk of antidepressantrelated death was significantly lower during treatment but the risk was significantly increased after withdrawal of antidepressants. However, the current research on antidepressant treatment was found that antidepressants could reduce mortality, which reduced the rate of mortality by 10% compared with non-users [4]. This contradictory finding might be explained by the high risk of death of the elderly and the limitations of the survey.…”
Section: Antidepressants and The Risk Of Deathmentioning
confidence: 90%
“…What's more, the risk of stroke or mortality associated with antidepressants is inconsistent. The increased stroke risk may be related to antidepressants, especially in the elderly [4]. This paradoxical result is mainly due to the fact that antidepressants have a range of side effects that can be detrimental to stroke recovery.…”
Section: Introductionmentioning
confidence: 99%
“…All patients underwent electrocardiography (ECG), carotid duplex ultrasound (CDU), and magnetic resonance imaging (MRI). The information of each patient was recorded as follows: history of TIA and stroke; current smoking and drinking behavior; previous risk factors such as hypertension, diabetes, and coronary artery disease [ 56 ]; medications used before MRI scan [ 57 ]; in-hospital assessment of arterial stenosis on CDU and magnetic resonance angiography (MR angiography); atrial fibrillation on ECG; brain infarction on diffusion-weighted imaging (DWI) and T2 fluid-attenuated inversion recovery (T2-FLAIR) [ 58 ]; and 1-year telephone follow-up for stroke and/or TIA episodes [ 59 ]. Participants with migraine, epilepsy, hemorrhage, leukoaraiosis, or psychiatric history were excluded from this study [ 60 ].…”
Section: Methodsmentioning
confidence: 99%